2008
DOI: 10.1093/cercor/bhn151
|View full text |Cite
|
Sign up to set email alerts
|

System A Transporter SAT2 Mediates Replenishment of Dendritic Glutamate Pools Controlling Retrograde Signaling by Glutamate

Abstract: Glutamate mediates several modes of neurotransmission in the central nervous system including recently discovered retrograde signaling from neuronal dendrites. We have previously identified the system N transporter SN1 as being responsible for glutamine efflux from astroglia and proposed a system A transporter (SAT) in subsequent transport of glutamine into neurons for neurotransmitter regeneration. Here, we demonstrate that SAT2 expression is primarily confined to glutamatergic neurons in many brain regions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 102 publications
4
71
1
Order By: Relevance
“…23 Glutamine synthesis can be inhibited by MSO, 24 and Gln transport can be blocked with MeAIB. 25 If the depressive behaviours caused by astrocyte ablation are due to lack of Gln supply from astroglia, inhibition of Gln synthesis in the PLC would be sufficient to evoke depressive behaviours.…”
Section: Blockade Of Gln Synthesis and Transport Increased The Duratimentioning
confidence: 99%
“…23 Glutamine synthesis can be inhibited by MSO, 24 and Gln transport can be blocked with MeAIB. 25 If the depressive behaviours caused by astrocyte ablation are due to lack of Gln supply from astroglia, inhibition of Gln synthesis in the PLC would be sufficient to evoke depressive behaviours.…”
Section: Blockade Of Gln Synthesis and Transport Increased The Duratimentioning
confidence: 99%
“…Indeed, glial cells are enriched with G-protein-coupled receptors, and their activation by glutamate, GABA, or other neurotransmitters are important endogenous triggers of PKC activation (Beckman et al, 1999). Complementary expression of both system A and non-system A transporters has been demonstrated on neurons, and it has been shown that the availability of glutamine regulates generation of the fast neurotransmitters (Rae et al, 2003;Jenstad et al, 2009;Solbu et al, 2010;Tani et al, 2010) and shapes the quantal size Liang et al, 2006;Fricke et al, 2007). Thus, SN1 may represent a key target for regulation of the glutamate/GABA-glutamine cycle (Fig.…”
Section: Functional Implications Of Sn1 Phosphorylationmentioning
confidence: 99%
“…According to the prevailing hypothesis, a significant amount of released glutamate and GABA is transported into perisynaptic astroglial processes, converted to glutamine, and then transported back to neurons for transmitter regeneration (Albrecht et al, 2007). Existence of such a glutamate/GABA-glutamine cycle has been bolstered by the characterization of a family of system A and system N transporters: SAT1 (Slc38a1) and SAT2 (Slc38a2) are selectively enriched in GABAergic and glutamatergic neurons, respectively, and inhibition of system A transport inhibits neuronal transmitter generation and synaptic transmission Liang et al, 2006;Jenstad et al, 2009;Solbu et al, 2010). System N transporter SN1, selectively expressed on astroglial processes ensheathing synapses, mediates release of glutamine and furnishes neurons with the primary neurotransmitter precursor (Chaudhry et al, 1999(Chaudhry et al, , 2001Boulland et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…SAT1 is expressed in the somatodendrites of neurons in brain regions enriched in GABAergic neurons, and its proximity to VGAT, the vesicular GABA transporter indicates that it might be related to glutamine uptake as a prerequisite to replenish the GABA neurotransmitter pool (Solbu et al, 2010;Varoqui et al, 2000). SAT2 is more ubiquitously expressed, being found localized mainly in somatodendrites and axons of glutamatergic neurons Jenstad et al, 2009). The importance of this transporter has been demonstrated by employing MeAIB (methylamino-iso-butyric acid), an inhibitor of system A, able to reduce glutamine uptake, which consequently diminishes the intracellular concentration of glutamate (Jenstad et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…SAT2 is more ubiquitously expressed, being found localized mainly in somatodendrites and axons of glutamatergic neurons Jenstad et al, 2009). The importance of this transporter has been demonstrated by employing MeAIB (methylamino-iso-butyric acid), an inhibitor of system A, able to reduce glutamine uptake, which consequently diminishes the intracellular concentration of glutamate (Jenstad et al, 2009).…”
Section: Introductionmentioning
confidence: 99%